2018
DOI: 10.1166/asl.2018.12063
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Undergraduates’ Self-Assessment in Delivering Technical Oral Presentations in ESL Context

Abstract: In recent years, alternative assessments have progressively gained attention in L2 speaking. An area which has received significant attention in the ESL literature has been the implementation of self-assessment strategy. The purpose of the present study is to find undergraduates' perceptions pertaining to the use of self-assessment on technical oral presentations. In order to achieve this aim, the study conducted 113 engineering undergraduates from the Faculty of Civil Engineering & Earth Resources to be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These conditions can increase students' information and knowledge. In addition, social networks can enable students to discussion effectively to solve their class problems, as an effective tool used for communication about what they learn [29].…”
Section: Specification Resultsmentioning
confidence: 99%
“…These conditions can increase students' information and knowledge. In addition, social networks can enable students to discussion effectively to solve their class problems, as an effective tool used for communication about what they learn [29].…”
Section: Specification Resultsmentioning
confidence: 99%
“…However, it also poses some challenges, whether done individually or collaboratively. One of the most common issues that students face is related to the anxiety or nervousness of performing in front of an audience (see Al-Nouh et al, 2015;Al-Darwish & Taqi, 2015;Benraghda et al, 2018;Chen, 2015;Hasanah et al, 2013;Okada et al, 2017;Tian & Mahmud, 2018). This feeling of nervousness is something that the students might feel the moment they know they would have to perform in front of the public (Al-Darwish & Taqi, 2015) because they believe that doing an oral presentation is difficult (Whai & Mei, 2012) or simply because they are just not confident (Whai & Mei, 2012).…”
Section: Challenges Students Face In Classroom Oral Presentationsmentioning
confidence: 99%
“…Thinking that they do not have adequate language mastery is one of the common issues that the students face, which relates closely to their nervous feeling. Mastery can relate to the lack of language proficiency in general (Chen, 2015;Hasanah et al, 2013;Whai & Mei, 2012) or something more specific, such as pronunciation (Chen, 2015;Al-Darwish & Taqi, 2015;Okada et al, 2017) vocabulary (Benraghda et al, 2018), and oral proficiency (Tian & Mahmud, 2018). Szyszka (2011) found a negative correlation between the students' self-perception on their pronunciation and language anxiety.…”
Section: Challenges Students Face In Classroom Oral Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…SA which is also named as self-rating, self-evaluation or self-appraisal has been frequently used to enhance tertiary studentcentered learning. Many studies concluded that SA strategy was reliable (Benraghda & Radzuan, 2018;Salehi & Daryabar, 2014). In this regard, the reliability of the assessment referred to the consistency and steadiness of the scores produced by a measurement instrument that could be determined in numerous ways.…”
Section: Introductionmentioning
confidence: 99%